ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 3 PADANG - Gebi Febri Delsi (Jurnal Edukasi dan Penelitian Matematika, 2021)
Analysis of students' ability to solve mathematical problems is one of the important things to do to determine students' ability to solve application problems from everyday life. Based on the data in the field, the tenth grade students of SMAN 3 Padang are thought to have low problem solving skills. This research approach is descriptive qualitative research. The results showed that the average score of the ability to solve mathematical problems in indicator 1 was 0.73 with sufficient category, indicator 2 was 0.74 with sufficient category, indicator 3 was 0.63 with sufficient category, indicator 4 was 0.22 with very less category. Keywords–  Mathematical Problem Solving ability